A campesinidade em Iraí de Minas - MG : estratégias de reprodução social no cerrado mineiro - Genaro, Felipe (2016)
The transformations on the organization of space in the region of Triângulo Mineiro / Alto Paranaíba from the modernization of agriculture, specifically in Iraí de Minas and the construction of hydroelectric Nova Ponte reflected in the (re) organization of regional space causing greater concentration of resources on large properties and excluding the production process a significant number of farmers living there for generations. Despite the advance of modernization, such projects do not result in a smooth, orderly process, however contradictory and producer of inequalities and inconsistencies One of the key projects for the consolidation of this model was PRODECER (Japanese-Brazilian Cooperation Program for the Development of the Savannahs) representing a new step in the appropriation of space in the Cerrado. Small producers of Iraí de Minas used the lands that were considered favorable to ensure their livelihood, but they were submerged by the dam. However they managed to stay on the field and recreate all the time reproductive strategies of their ways of life, guided by a campesinidade . In front of the Cerrado modernization projects, small farmers of Irai de Minas, especially those engaged in dairy farming, are currently found \"stranded by modernity\", but continue their country life, and still try to earn their living and their family.